Commodity Prices and Dry Bulk Shipping Stock Returns - Michail, Nektarios A.; Melas, Konstantinos D. (My University, 2023)
We explore the relationship between the returns of 64 dry bulk shipping company stock prices and the main 15 commodities that bulk carriers transport. Using a principal component analysis to reduce the dimensionality of the commodities dataset and a panel methodology, we find that a change in the commodity price principal component would result in a 0.6% change in the returns of the shipping stock prices. Minerals appear to have a stronger impact, as a 1% change in the minerals principal component results in a 1.1% change in the returns. This is mainly due to the fact that minerals account for larger trade volumes in the dry bulk market and they employ mostly bigger vessels, while the price of Brent oil is also an important factor affecting shipping stock prices.
Keywords: Commodities; Dry bulk market; Principal component analysis; Shipping